2010
DOI: 10.1161/atvbaha.109.193896
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT Signaling Pathway Regulates Nox1 and Nox4-Based NADPH Oxidase in Human Aortic Smooth Muscle Cells

Abstract: Objective-Oxidative stress mediated by Nox1-and Nox4-based NADPH oxidase (Nox) plays a key role in vascular diseases. The molecular mechanisms involved in the regulation of Nox are not entirely elucidated. Because JAK/STAT regulates many genes linked to inflammation, cell proliferation, and differentiation, we questioned whether this pathway is involved in the regulation of Nox1 and Nox4 in human aortic smooth muscle cells (SMCs). Methods and Results-Cultured SMCs were exposed to interferon ␥ (IFN␥) for 24 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 41 publications
(19 reference statements)
2
107
0
Order By: Relevance
“…Several transcription factors and the corresponding cis-elements have been implicated in transcriptional regulation of Nox4, implying the multifactorial nature of this process. These include Smad3 (39,45), which through AP1/Smad-binding elements (39) couples Nox4 to TGF␤ signaling and thereby fibrogenesis; Hif1␣ (58), Nrf2 (59) and Oct-1 (60), which link Nox4 expression to ROS generation per se under conditions of hypoxia, hyperoxia, and shear stress; NFB (61) and STAT proteins (62), mediators of inflammatory gene expression; and E2F (63), a regulator of proliferation. This study enriches this picture by two important findings indicating that MRTF and TAZ/YAP, two main cytoskeleton-regulated transcrip-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors and the corresponding cis-elements have been implicated in transcriptional regulation of Nox4, implying the multifactorial nature of this process. These include Smad3 (39,45), which through AP1/Smad-binding elements (39) couples Nox4 to TGF␤ signaling and thereby fibrogenesis; Hif1␣ (58), Nrf2 (59) and Oct-1 (60), which link Nox4 expression to ROS generation per se under conditions of hypoxia, hyperoxia, and shear stress; NFB (61) and STAT proteins (62), mediators of inflammatory gene expression; and E2F (63), a regulator of proliferation. This study enriches this picture by two important findings indicating that MRTF and TAZ/YAP, two main cytoskeleton-regulated transcrip-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…The increased 12/15-LOX mRNA levels point to a dominant effect of transcriptional events, however. (2) Both STAT1 and STAT6 will likely regulate additional genes in the ischemic brain, including the NADPH oxidases NOX1 and NOX4, 38 and the cyclooxygenase COX-2. 39 Furthermore, AKT phosphorylation was increased, and caspase-3 cleavage decreased in STAT1 knockouts subjected to focal ischemia, 14 and the impact of 12/15-LOX on these events should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nox4 appears to generate H 2 O 2 , although the primary product is probably O 2 -, which is rapidly dismutated to H 2 O 2 (202,232). Nox4 contributes to basal ROS production through its constitutive activity and to increased ROS generation when induced by Ang II, glucose, tumor necrosis factor a, and growth factors (90,127). Recent studies have identified a 28-kDa Splice Variant of Nox4 located in the nucleus of vascular cells, which may be important in pathophysiologic effects through modulation of nuclear signaling and DNA damage (9).…”
Section: Nox4mentioning
confidence: 99%